EFFECT OF MECHANOACTIVATION ON THE CORROSION INHIBITOR EFFICIENCY OF 1-PHENYL – 1 - CYCLOHEXYLMETHYL – BENZOTRIAZOLE - S.M, Reshetnikov; A.N, Lubnin; O.M, Kanunnikova; V.V, Aksenova; V.V, Muhgalin; A.A, Solovyev; A.I, Altsybeeva; V.I, Ladyanov (IJRDO-Journal of Applied Science, 2017)
During ball milling, a decrease in the number of unsaturated bonds and the destruction of the heterocyclic molecule structure of 1 -phenyl – 1 - cyclohexylmethyl – benzotriazole are observed. Degradation products are less toxic and exhibit increased inhibitory properties compared to the original inhibit-ROM. In borate buffer the inhibitory properties of the initial and mechanoactivated inhibitor appear directly after adding to the corrosive solution. In chloride-sulphate solution inhibitory properties appear a few hours after adding to the solution.